Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.5539/ass.v9n11p189
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Child Communication and Self Concept among Malays Adolescence

Abstract: This research was conducted to determine the relationship between children's communication with their parents and self concept among Malay adolescence. The Questionnaire of Communication Exercise for Teenagers (1971) was used to measure the level of communication between child and parents whiles the second questionnaire, Harter Self Perception Profile for Adolescents Scale (1986) was used to measure the child's self concept. This quantitative descriptive study selected 300 consist adolescence aged 15-16 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…According to a research conducted in Malaysia with adolescents, it has been found that communication plays a significant role in emerging self-concept of daughters. Furthermore, the analysis could also be supported by their collectivist nature as a society where harmony is emphasized along with ability to nourish their familial relationships through practices of active communication (Razali & Razali, 2013). Thus, the current research also denotes a strong positive correlation between communication of mothers and fathers with daughters' self-concept.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…According to a research conducted in Malaysia with adolescents, it has been found that communication plays a significant role in emerging self-concept of daughters. Furthermore, the analysis could also be supported by their collectivist nature as a society where harmony is emphasized along with ability to nourish their familial relationships through practices of active communication (Razali & Razali, 2013). Thus, the current research also denotes a strong positive correlation between communication of mothers and fathers with daughters' self-concept.…”
Section: Discussionmentioning
confidence: 69%
“…The age range selected was from 18 years to 20 years. According to research the age range of young adulthood plays a vital role in personality development of daughters (Razali & Razali, 2013). In order to be precise while collection of data these two years were considered.…”
Section: Methods Samplementioning
confidence: 99%
“…For this study, the three parenting styles which are authoritative, authoritarian and permissive were formed based on two indiced of Baumrind (1971) which are demand index (demandingness) and responsive index (responsiveness) are used as themes for parenting styles. Parenting style refers to the behavior practiced by the parents to guide their children into becoming a successful and productive person (Razali & Razali, 2013). The three parenting styles are explained as below.…”
Section: Research Literaturementioning
confidence: 99%